Spatial and temporal patterns of flow intermittency in a Mediterranean basin using the SWAT+ model. Issue 2 (25th January 2023) - Llanos-Paez, Oriana; Estrada, Laia; Pastén-Zapata, Ernesto; Boithias, Laurie; Jorda-Capdevila, Didac; Sabater, Sergi; Acuña, Vicenç
ABSTRACT: Non-perennial rivers and streams are ubiquitous. Nonetheless, our understanding of their hydrological patterns is minimal. Hydrological models are powerful tools to study and characterize hydrological patterns, but few can simulate extremes such as non-flow events. We aimed to capture and accurately simulate the flow intermittency spatial and temporal patterns in a Mediterranean river basin with the restructured Soil and Water Assessment Tool (SWAT+). We calibrated the model using a multi-objective optimization algorithm and using data from two gauging stations in the mainstream for the period 2000–2020. Furthermore, we validated the flow intermittency simulations against stage data series at 14 stations. The results indicated that the model accurately simulates flow intermittency and low flows in the study period. We observed a significant variation in flow intermittency in both space and time with a remarkable inter-annual variability. We also observed an increase in flow intermittency over the study period.